Human Resource Development Strategies Through Training in Order to Optimize the Quality of Company Employees: A Literature Review - Moh. Rodiaminollah; Moh. Ali Fahmi; Lu’lu’ Nurul Qomariyah; Masjadin Masjadin (CV. Civiliza Publishing, 2026)
Business competition in the current global era and the rapid development of technology require business people, in this case companies are required to be able to compete quickly, accurately and effectively. Training and development for employees is one of the wise ways taken by companies in an effort to pursue business acceleration that cannot be compromised, but looking at the conditions that occur in the business world today, there are still many companies in Indonesia that experience obstacles and challenges in designing training programs that are in accordance with what the company wants to be effective and efficient. This research aims to analyze human resource development strategies in this case employees through training based on national and international literature to design performance that can effectively help employee quality. The method used is an integrative literature review by analyzing 45 journal articles, 8 textbooks, and 5 official reports from Indonesian government institutions for the 2018-2025 period. The data analysis technique uses qualitative content analysis to identify key themes, patterns, and concepts related to effective training strategies. The results show that an optimal training strategy consists of four main components: performance-based training needs analysis, competency-based program design, contextual and participatory training methods, and work-based training evaluation. In addition, three Indonesian contextual factors were found that affect the effectiveness of training: technological readiness, organizational culture, and the role of the government. The 4P Training Strategy Model is designed as a fairly practical framework by integrating planning, implementation, monitoring, and assessment. The most important factors supporting success include top management commitment, organizational learning culture, and learning technology support. In Indonesia, the main challenges include limited MSME budgets, low digital literacy of trainers, and lack of optimal integration of training with performance management systems. The practical implication of this study is the need for companies to develop training policies that are aligned with business strategies and use the modified Kirkpatrick evaluation model according to the Indonesian context. This research provides a theoretical contribution in the form of integrating the concepts of human resource development, andragogy, and performance management in the context of companies in Indonesia. The recommendation for the next research is to test this training strategy model empirically in the MSME sector and labor-intensive industries.